2018
DOI: 10.1164/rccm.201710-2107oc
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and Biology of Human Small Airway Epithelial Club Cells

Abstract: These observations provide novel insights into the molecular phenotype and biologic functions of the human club cell population and identify basal cells as the human progenitor cells for club cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 49 publications
13
73
0
Order By: Relevance
“…Recently Choudhary et al (2005) reported that among human organs CYP4B1 transcripts were found predominantly in the lung (70% of organ distribution, the remainder in heart, skeletal muscle and kidney; none in the liver). Zuo et al (2018) demonstrated in samples-gained by bronchoscopy and by scraping from the human small airways epithelial Clara (Club) cells-transcripts of the following CYPs: 2F1 (very abundant), 4B1 (abundant), 2J2, 51A1, as well as CYB5R3 (cytochrome b5 reductase 3).…”
Section: Xenobiotica-metabolizing Enzymes In the Human Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Choudhary et al (2005) reported that among human organs CYP4B1 transcripts were found predominantly in the lung (70% of organ distribution, the remainder in heart, skeletal muscle and kidney; none in the liver). Zuo et al (2018) demonstrated in samples-gained by bronchoscopy and by scraping from the human small airways epithelial Clara (Club) cells-transcripts of the following CYPs: 2F1 (very abundant), 4B1 (abundant), 2J2, 51A1, as well as CYB5R3 (cytochrome b5 reductase 3).…”
Section: Xenobiotica-metabolizing Enzymes In the Human Lungmentioning
confidence: 99%
“…Leclerc et al (2011) observed in the human bronchial mucosa high levels of FMO2 and moderate levels of FMO5 transcripts, and in pulmonary parenchyma high levels of both of them. Zuo et al (2018) demonstrated in samples-gained by bronchoscopy and by scraping from the human small airways epithelial Clara (Club) cells-transcripts of FMO2.…”
Section: Non-cyp Oxidoreductases (Tables 2 9)mentioning
confidence: 99%
“…Two genes were significantly upregulated in transplantable lungs, MTRNR2L1, (encoding humanin-like 1), and SCGB1A1, a secretoglobin expressed by club cells (39). The humanin gene family encodes for highly similar small secretory 21-24 amino acid peptides (57) that have been shown to be protect cells from oxidative stress, starvation and hypoxia (41) and MTRNR2L1 transcription is increased by oxidative stress and toll-like receptor 4 agonists (58), therefore, its upregulation may enhance cellular integrity in lungs in the face of cell stressors associated with the organ procurement process.…”
Section: Discussionmentioning
confidence: 99%
“…A recent single cell RNA sequencing analysis of small airways cells identified SCGB1A1 (also known as uteroglobin or CC10) as a canonical marker of club cells, and cell trajectory analysis indicate that they may have the capacity to both de-differentiate into basal cells (with stem capacity) and trans-differentiate into ciliated epithelial cells. Analysis of cell-specific gene expression suggests that club cells may also play novel roles in host defence and have anti-protease activity via the expression of α1-antitrypsin (an important neutrophil elastase inhibitor) and SLPI (secretory leucoprotease inhibitor, a potent serine protease inhibitor) (39). SCGB1A1 has been shown to have direct anti-inflammatory actions inhibiting NFkB activation and CXCL8 secretion in airway epithelial cells(42) (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation